CROWDFUNDING FOR DEVELOPING WAQF LAND A STUDY ON MALAYSIA - Hapsari, Meri Indri; Bin, Mohamed Asmy; Muhammad, Mustafa Omar; Dausa, Jarita (Jurnal Syarikah : Jurnal Ekonomi Islam, 2020)
This present study aims to develop an alternative model of financing that address the problems of waqf land financing in Malaysia, analyse the probability that waqf institution will use the proposed model and recommend policies to enhance the optimisation of crowdfunding for developing waqf land. This study focuses on potential donors in the four states in Malaysia, namely Pahang, Pulau Pinang, Selangor and Johor since these areas have significant waqf lands. The analysis is conducted using statistical analysis and logistic regression analysis. The study finds that there is a high probability of donors willing to use the proposed model (CWM), particularly among non-married donors, females, low-middle income donors, and those with more awareness of crowdfunding and waqf.